Eufemisme dan Disfemisme pada Judul Berita E-Sumatera Ekspres : Edisi Agustus-Oktober 2024 - Rima Harista; Masnunah Masnunah; Hayatun Nufus (Pusat Riset dan Inovasi Nasional, 2025)
News headline writing is one of the most critical aspects because it can affect readers' perceptions of the issues reported. The headline is the main thing that can attract the attention of readers, therefore writing a good and correct headline can affect the way readers conclude the content of the news. Based on this, the problem in this study is how the form and function of euphemisms and dysphemisms used in E-Sumatera Ekspres news headlines, especially political, criminal and environmental headlines (August-October 2024 edition). The purpose of this study is to identify and analyze the use of euphemisms and dysphemisms in E-Sumatera Ekspres headlines (August-October 2024 edition). The results of the study found a total of 9 euphemism data consisting of 2 data of euphemism in the form of figurative expressions, 1 data of euphemism in the form of remodeling, 3 data of euphemism in the form of circumlocution, and 3 data of euphemism in the form of one word to replace another word. Furthermore, 22 data of dysphemism were found, consisting of 15 data of dysphemism in the form of figurative expression, 3 data of dysphemism in the form of metaphor, 1 data of dysphemism in the form of flipansi, 2 data of dysphemism in the form of remodeling, and 1 data of dysphemism in the form of circumlocution. The data shows that not all categories of euphemisms and dysphemisms described by Allan and Burridge are found in the research data. The research method used is descriptive method. This research reveals that the use of euphemisms aims to soften the delivery of sensitive information to make it more acceptable to readers, while dysphemisms are used to attract attention by accentuating dramatic or controversial aspects in the news.